How to lose all your friends - Carlson, Nancy L. (New York : Viking, 1993)
Offers advice on the kinds of things to do if you don't want to have any friends.
Elem. School Library Collection.
School Library Journal.
Book Links (A.L.A.).
2.5
K-3
Keywords: Behavior -- Fiction; Friendship -- Fiction; Human behavior; Friendship -- Fiction; Behavior -- Fiction; Friendship -- Fiction